Q: What is 6x plus 13 equals 97-6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

10

x=-7/13

6x-2=x+135x=15x=3

6x+13=-2x-19 so 8x=-19-13=-32 so x=-4

6x+13 is just 6x+13 you can not combine the terms because they are not like terms. ifyou make this expression equal a value... lets say 1 then you can find a value for "x" 6x+13=1 6x+13-13=1-13 6x=-12 x=-2

Related questions

6x + 8 = 13, 6x = 13 - 8, 6x = 5, x = 5/6

10

x=-7/13

6x-2=x+135x=15x=3

6x+13=-2x-19 so 8x=-19-13=-32 so x=-4

x2 + 6x - 2 = 0 x2 + 6x + 9 = 13 (x + 3)2 = 13 x + 3 = ± √13 x = -3 ± √13

6x+13 is just 6x+13 you can not combine the terms because they are not like terms. ifyou make this expression equal a value... lets say 1 then you can find a value for "x" 6x+13=1 6x+13-13=1-13 6x=-12 x=-2

4x +13 = 93-6x. Adding 6x to each side gives: 10x+13 = 93. Subtracting 13 from each side gives: 10x = 80. Dividing both sides by 10 gives: x = 8.

(9,6)

6x+x = 7x

Subtract: 2x = -20Divide by 2: x = -10

6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.